A review on the application of horizontal heat pipe heat exchangers in air conditioning systems in the tropics - Yau, Y.H.; Ahmadzadehtalatapeh, M. (Elsevier, 2010)
A literature review on the application of horizontal heat pipe heat exchangers for air conditioning in tropical climates was conducted. This paper focused on the energy saving and dehumidification enhancement aspects of horizontal heat pipe heat exchangers. The related papers were grouped into three main categories and a summary of experimental and theoretical studies was made. It was revealed that although there are a number of valuable researches on the impact of heat pipe heat exchangers on the energy consumption and dehumidification enhancement of air conditioning systems in the tropics, but only limited research work on the application of horizontal configuration heat pipe heat exchangers in air conditioning systems has been carried out in these regions. Therefore, it needs more research to deepen the under standing of the benefits of this heat recovery device in the air conditioning systems. On the basis of results obtained from the reviewed research studies, the application of horizontal heat pipe heat exchangers in terms of energy saving, dehumidification enhancement and condensate drainage is recommended for the tropics. (C) 2009 Elsevier Ltd. All rights reserved